Digitalization of Payments and Financial Management for MSMEs at Warkop Gondrong Makassar - M. Yusuf K; Sri Wahyuni; Ismawati; Muh. Khaidir Ramadhan; ⁠Ahmad Izzaturrahim (www.amertainstitute.com, 2025)
The community service project with the theme UMKM GO DIGITAL: